Synthesis of hexopyranosyl pyrimidine homonucleosides. Issue 3 (1st February 2021) - Verma, Vineet; Maikhuri, Vipin K.; Khatri, Vinod; Singh, Ankita; Prasad, Ashok K.
Abstract: A simple and convenient methodology has been developed for the synthesis of novel hexopyranosyl pyrimidine homonucleosides and hexopyranosyl double-headed pyrimidine homonucleosides from the corresponding native sugars, d -glucose and d -mannose. Thus, hexose sugars were converted to 2, 6-anhydro-3, 4, 5, 7-tetra- O -benzyl-heptitols and 2, 6-anhydro-3, 4, 5-tri- O -benzyl-heptitols by recently developed procedure of Khatri et al. Further, mono- and di-hydroxy 2, 6-anhydro-heptitols were converted to their corresponding mono- and di-tosylated derivatives, which were then translated into hexopyranosyl homonucleosides and double-headed homonucleosides by reaction with uracil and thymine in 40–50 and 27–73% overall yields from tetra- and tri- O -benzylated anhydro-heptitols. Graphical Abstract: